Moderasi Ukuran Perusahaan terhadap Pengaruh Leverage dan Pertumbuhan Penjualan pada Profitabilitas (Jurnal Kendali Akuntansi, 2025)
This study aims to analyze the role of company size as a moderator variable in the relationship between profitability and leverage and sales growth in manufacturing companies in the basic industry and chemical sectors listed on the Indonesia Stock Exchange (IDX) for the 2020–2023 period. The research method used is a quantitative approach with purposive sampling techniques, so that 56 sample data that meet the research criteria are obtained. Data analysis was carried out using Moderated Regression Analysis (MRA) with the help of SPSS software version 30. The results show that leverage does not have a significant effect on profitability, while sales growth is proven to have a significant effect on profitability. Furthermore, company size has not been shown to moderate the relationship between leverage and profitability, but it does play a significant role in moderating the relationship between sales growth and profitability. These findings support the Pecking Order theory, which emphasizes that companies with larger sizes tend to have wider access to funding so that they are able to strengthen the influence of sales growth on profitability. This research provides a theoretical contribution in enriching the literature on factors that affect profitability, as well as a practical contribution to company management in formulating more effective financial and growth strategies. Thus, the size of the company proves to be an important factor to consider in the analysis of financial performance, particularly in the context of the relationship between sales growth and profitability.